Millennial generation in Bangladesh : their life strategies, movement, and identity politics - "Perceiving Contemporary Young Generation in Bangladesh: their Life Strategies and Identity Politics under Globalization" (Conference) (2019 : Dhaka, Bangladesh); Minamide, Kazuyo, 1975-; Nihon Gakujutsu Shinkōkai (Dhaka : University Press Limited, 2022)
Papers presented at the International symposium "Perceiving Contemporary Young Generation in Bangladesh: their Life Strategies and Identity Politics under Globalization" in February 2019 at Department of Anthropology of Jahangirnagar University in Dhaka; funded and organized by Japan Society for the Promotion Science (JSPS).
Includes bibliographical references and index.
ESS
Book Finder International
Keywords: Youth -- Bangladesh -- Congresses; Youth -- Bangladesh -- Social conditions -- Congresses; Politics and culture -- Bangladesh -- Congresses; Popular culture -- Bangladesh -- Congresses; Ethnicity -- Bangladesh -- Congresses; Identity politics -- Bangladesh -- Congresses; Social sciences